Medical Therapy in Venous Thromboembolism - Eichinger, Sabine; Kyrle, Paul A. (Seminars in Respiratory and Critical Care Medicine, 2012)
Immediate intense anticoagulation with parenteral anticoagulants (heparin or fondaparinux) followed by vitamin K antagonists is the current standard therapy for deep vein thrombosis (DVT) or nonmassive pulmonary embolism. In the future, new oral anticoagulants may replace not only vitamin K antagonists but also initial parenteral anticoagulation. Duration of anticoagulation should be at least 3 months because shorter courses double the recurrence rates. More prolonged anticoagulation therapy may be warranted in the presence of specific clinical risk factors. Global markers of coagulation, particularly D-dimer, may discriminate low- and high-risk patients. Models that combine clinical characteristics and laboratory markers further improve prediction of the recurrence risk in individual patients, but these models await validation before they can be applied in routine care.
Keywords: deep venous thrombosis; pulmonary embolism; venous thromboembolism; anticoagulation